1997
DOI: 10.7326/0003-4819-126-9-199705010-00006
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Deep Venous Thrombosis of the Upper Extremities

Abstract: This preliminary study indicates that the prevalence of hypercoagulable states is low in patients who have primary deep venous thrombosis of the upper extremities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 0 publications
2
64
2
Order By: Relevance
“…In the first case-control study with a total of 36 patients with DVTUE, Martinelli et al found a prevalence of abnormalities in the coagulation system of only 8% [6]. This was comparable with a control group of individuals without thrombosis.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In the first case-control study with a total of 36 patients with DVTUE, Martinelli et al found a prevalence of abnormalities in the coagulation system of only 8% [6]. This was comparable with a control group of individuals without thrombosis.…”
Section: Discussionmentioning
confidence: 86%
“…The role of these low-titer antibodies in the pathogenesis of venous thrombosis is still a matter of debate [10]. The prevalence of APA is strongly dependent upon the methods used, which were not properly described in some of the previous studies [6,11]. Also the time point of testing for antibodies is important, because APA may be transient and therefore missed if the moment of blood sampling is long after the thrombotic event.…”
Section: Discussionmentioning
confidence: 99%
“…Ruggeri et al [20] reported a congenital coagulation defect in only two out of 27 patients (7.4%) with upper-limb thrombosis and positive anticardiolipin antibodies in 4 cases (14.8%). Martinelli et al [5] found an inherited hypercoagulable status in only three out of 36 patients (8%) with spontaneous UEDVT. This prevalence was similar to a control healthy group but significantly lower than a cohort of patients with lower-limb DVT (56%).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies reported an increased evidence that hyperhomocysteinemia is a risk factor for venous thrombosis and that the association of this coagulation abnormality with other genetic or acquired thrombophilic defects further increased this risk. Reviewing the series published about prevalence of thrombophilic states in UEDVT, only the one by Martinelli et al [5] evaluated plasma homocysteine levels and found hyperhomocysteinemia in 6% of patients with UEDVT and in 14% with lower extremities DVT. In our series, we found high plasma homocysteine levels in five patients (16%) with a combined diagnosis of hyperhomocysteinemia and lupus anticoagulant in two of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation